1998
DOI: 10.1016/s0735-1097(98)00472-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mitral inflow and superior vena cava Doppler velocities in chronic obstructive pulmonary disease and constrictive pericarditis

Abstract: Despite a similar respiratory variation in mitral E wave velocities, mitral inflow variables in chronic obstructive pulmonary disease are less restrictive compared with those in constrictive pericarditis. More importantly, patients with chronic obstructive pulmonary disease show a marked increase in inspiratory superior vena cava systolic forward flow velocity, which is not seen in patients with constrictive pericarditis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 16 publications
0
49
0
Order By: Relevance
“…67 Wide swings in the E wave velocity may also occur in patients with respiratory disease, but these are associated with marked respiratory variation in the superior vena caval flow velocity (typically Ͼ20 cm/s), whereas the variation with pericardial constriction is less. 46,68 Other findings in constrictive pericarditis include preserved diastolic mitral annular velocity, rapid diastolic flow propagation to the apex, and diastolic mitral regurgitation. 69 …”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…67 Wide swings in the E wave velocity may also occur in patients with respiratory disease, but these are associated with marked respiratory variation in the superior vena caval flow velocity (typically Ͼ20 cm/s), whereas the variation with pericardial constriction is less. 46,68 Other findings in constrictive pericarditis include preserved diastolic mitral annular velocity, rapid diastolic flow propagation to the apex, and diastolic mitral regurgitation. 69 …”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…We did not routinely perform preload reduction to unmask Doppler respiratory variation. 10 However, a recent study by Shimizu et at 26 showed that MVG is relatively independent of loading conditions. Therefore, we can assume that MVG measurements should be similar to those obtained with preload reduction.…”
Section: Limitationsmentioning
confidence: 97%
“…5,6 However, respiratory variation can also be observed in patients with chronic obstructive airway disease. 10 Also, a considerable percentage of CP patients do not demonstrate respiratory variation in their blood-flow velocities. 6 Oh et al 11 proposed that in this group of patients, additional echocardiographic tests to reduce preload may help unmask or enhance respiratory variation on transmitral Doppler flow.…”
mentioning
confidence: 99%
“…This stands in contrast to greater (>35%) changes in superior vena cava forward flow velocity in patients with obstructive lung physiology in whom there is ventricular interdependence and ventricular septal shift because of pronounced respiratory swings in intrathoracic pressure. 14 Because severe obstructive lung disease or other conditions associated with increased respiratory effort may lead to abnormal ventricular septal wall motion and respiratory variation in mitral inflow velocity similar to that seen in constrictive pericarditis, this differentiating feature is clinically useful.…”
Section: Other Echocardiographic Findingsmentioning
confidence: 99%